CARBON FIBER AND PLANT FIBER COMPOSITE TECHNOLOGY DEVELOPMENT IN HIGH STRENGH PARTS - Pigožnis, Kārlis; Teirumnieks, Edmunds (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
Natural abundance, low density, high strength per unit weight, and biodegradability of natural materials, specifically natural fibres, render them attractive for other reinforcements. In order to clarify the effect of natural fibers as reinforcments upon the tensile strength of polyacrylonitrile (PAN)-based carbon fibres, experimental as well as theoretical studies have been performed. A new material developing has been made in combining different fiber materials and testing them for strengh.